2017
DOI: 10.12688/f1000research.12404.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Vietnamese co-authorship patterns in social sciences with basic network measures of 2008-2017 Scopus data

Abstract: Background: Collaboration is a common occurrence among Vietnamese scientists; however, insights into Vietnamese scientific collaborations have been scarce. On the other hand, the application of social network analysis in studying science collaboration has gained much attention all over the world. The technique could be employed to explore Vietnam’s scientific community. Methods: This paper employs network theory to explore characteristics of a network of 412 Vietnamese social scientists whose papers can be fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
4
18
0
2
Order By: Relevance
“…Moreover, even among scientists who have published in indexed international journals, there have been signs of its low sustainability, such as the lack of information distribution in the co-authorship network, or a high level of reliance on a few highly connected members in the networks (Ho et al, 2017). Results suggested that only specific groups such as first-authorship and seniority (age 40 -50) appeared to have crucial contributions in the community (Vuong et al, 2017;Vuong et al, 2018).…”
Section: Overview Of Vietnamese Ssh Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, even among scientists who have published in indexed international journals, there have been signs of its low sustainability, such as the lack of information distribution in the co-authorship network, or a high level of reliance on a few highly connected members in the networks (Ho et al, 2017). Results suggested that only specific groups such as first-authorship and seniority (age 40 -50) appeared to have crucial contributions in the community (Vuong et al, 2017;Vuong et al, 2018).…”
Section: Overview Of Vietnamese Ssh Productivitymentioning
confidence: 99%
“…Fortunately, the establishment of NAFOSTED in 2008, followed by two new policies in 2014 and 2017 ( Figure 1), appeared to trigger positive changes in terms of research output of SSH (Ho et al, 2017). The number of ISI-indexed publications from Vietnam thus has been rising five times since 2009 (Adams et al, 2019).…”
Section: Overview Of Vietnamese Ssh Productivitymentioning
confidence: 99%
“…Sự ra đời của tạp chí mở hoàn toàn F1000Research cách đây vài năm phản ánh xu hướng đó. Đã có một số tác giả Việt Nam công bố trên tạp chí này và người đọc có thể xem đầy đủ biên bản phản biện và trả lời của các tác giả [4,5] . Xu hướng này mang đến những giá trị mới cho công ích khoa học và giúp việc đánh giá uy tín học thuật toàn diện hơn về mọi mặt.…”
Section: Giá Trị Của Phản Biện Là Gì?unclassified
“…To support this, future centers of excellence at universities that aim to support quality research should consider promoting collaborative research operations, where senior and prolific researchers, as project leaders, would also serve as mentors and in-house reviewers to novice researchers [58][59][60].…”
Section: Policy Implicationsmentioning
confidence: 99%